The Image as Metaphor: An Exploration Into the Metaphorical and Experiential Operations of the Installed Image - Fong, Helen (Auckland University of Technology, 2003)
This is a practical art project intended to complete research into an Image that has concentrated creative energies over the past four years. It is accompanied by a 6000 word exegesis contextualising the practical work, including discussion of past work, and the project methodology. This has been a reflective year in which past research both academic and studio has been reviewed. The main focus is on consideration of the concept of metaphor, the role it has played in past studio research and painting works, and the possibilities it may hold for a further series. Major emphasis is placed on studio practice, the aim being to create an installation of works which implicate the spectator directly into reflection and construction of their own experience of the Image. The area of studio research is painting, involving also the processes of photography, printing and the further integration of computer technology into one’s process. As one probes deeper into the Image, issues of transparency and reflection assume greater importance and in line with this emphasis, transparent and reflective materials such as glass and perspex have been researched and experimented with for evaluation of the possibilities of their use in the installation. The aim of the installation is to develop ideas of 2002, in which a space that was open to all directions was created for the viewer to enter and consider translation No 4 of the Image. In light of the view that metaphor involves not only an understanding but also an experience of a concept, one hopes to extend this experiential aspect and create a series of spaces for the viewer to walk through and create their own experience of the Image.
Keywords: Art installations; New Zealand art; Art metaphor; Metaphor as concept